Utvärdering av en snabbtest för diagnostisering av hypokalcemi hos nötkreatur - Lundgren, Bo (2005)
Clinical signs of hypocalcaemia in dairy cows are easily recognized, and a rapid response to treatment generally confirms the diagnosis in the field. However, clinical signs of other disorders in cows, such as toxemia, calving paralysis, or muscoskeletal injury, may mimic those associated with hypocalcaemia. Therefore, making a diagnosis of hypocalcaemia on the basis of clinical signs alone may be difficult. In ambulatory veterinary practices, cow-side tests are useful to make the diagnosis and prognosis easier.